MERANCANG PESAN YANG EFEKTIF UNTUK IKLAN PRODUK UNSOUGHT - Puryandani, Siti (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2012)
Any decision taken in the field of marketing is called good if the decisions taken was always associated with an environment that is always changing and evolving. In connection with activities of integrated marketing communications (Integrated Marketing Communication / IMC) conducted marketers is to choose between using sales promotion, publicity, advertising or personal selling. Of course, the existence of competition should still be noted. However marketers should continue to try to make consumers feel more satisfied than when consuming the products of competitors. In this case the concept of customer satisfaction is maintained. In the consumer self there is a concept that can be exploited by emotional factors play a factor other than rational. In connection with the theme of the message to be designed for this type of product unsought, marketers need to be creative these roles.